Farm size: implications for social inequity among ethnic communities in a mountainous area of Vietnam. Issue 3 (27th May 2022) - Nguyen, Toai; Lawler, Susan; Paul, Warren; Goldoftas, Barbara; Huynh, Da
ABSTRACT: The disparity in access to agricultural land can be a source of social inequality, impeding community development in rural areas in many developing countries. Previous studies have identified factors that affect landholding size but have failed to understand operational farm size in the area with the coexistence of local indigenous people and internal immigrants. In this study, we conducted 121 interviews with farmers from the buffer zones of Vietnam's Bu Gia Map National Park to understand the determinants of operational farm sizes of farmers. The findings of this study demonstrate that indigeneity, female-male labor force ratio, education level of heads of households, training in agriculture, and residential communes are statistically significant in explaining the operational farm size of farmers. The findings of this study can support the government and practitioners in assisting community development by creating interventions to reduce social inequality based on socioeconomic profiles.